2011
DOI: 10.1097/scs.0b013e3181f7df35
|View full text |Cite
|
Sign up to set email alerts
|

Inferior Bundle (Fourth Band) of the Buccinator and the Incisivus Labii Inferioris Muscle

Abstract: The aim of this study was to clarify the morphologic and spatial relationships of the inferior bundle of the buccinator and the incisivus labii inferioris muscle (ILI) and their surrounding structures. The inferior bundle of the buccinator and the ILI were investigated in 40 hemifaces from Korean cadavers. The inferior bundle (or fourth band) of the buccinator muscle was observed in 14 (35%) of the 40 specimen sides. The ILI was found in 39 (97.5%) of the 40 specimen sides. The spatial relationships of the ILI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…Our literature review revealed that some authors believed the ILS to be the bony heads or accessory bundle of the OO [ 7 , 9 , 14 ]. We agree, because all the fibers of the i-ILS join the OO, and regarding the lower lip, the incisivus labii inferioris is an accessory muscle of the OO complex [ 21 - 22 ]. No literature has mentioned the common bony attachment of the nasalis and i-ILS, but Burkitt and Lightoller [ 5 ] presented a similar illustration, a triangular bony attachment, but each attachment was separate in their study.…”
Section: Discussionmentioning
confidence: 82%
“…Our literature review revealed that some authors believed the ILS to be the bony heads or accessory bundle of the OO [ 7 , 9 , 14 ]. We agree, because all the fibers of the i-ILS join the OO, and regarding the lower lip, the incisivus labii inferioris is an accessory muscle of the OO complex [ 21 - 22 ]. No literature has mentioned the common bony attachment of the nasalis and i-ILS, but Burkitt and Lightoller [ 5 ] presented a similar illustration, a triangular bony attachment, but each attachment was separate in their study.…”
Section: Discussionmentioning
confidence: 82%
“…The ILS has a more complicated course than the ILI. The ILS courses along the convex superior peripheral part of the OOr, blending with several muscles in the modiolar area, while the ILI courses laterally and upward along the lower mucolabial fold and blends with the OOr or buccinator below the level of the corner of the mouth 5 , 11 , 12 . The present study has clearly demonstrated several anatomical features of the ILS (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Burkitt and Lightoller (1926) 10 described that the ILS is well developed and that its fibers are of the same size and pigmentation as in the OOr in Aboriginal Australians. There have been several reports about the morphology of the ILI and its anatomical relationships with surrounding structures in humans 11 , 12 . However, there have been few reports about the anatomy of the ILS 13 .…”
Section: Introductionmentioning
confidence: 99%
“…However, we need to understand all the related mimetic muscles three dimensionally prior to discussing this space, because most of those mimetic muscles related to the oral cavity have been described via dissection from outside the face and not from an intraoral perspective. Also, most of the studies of the mimetic muscles used embalmed cadavers where it is difficult to retract the muscles and other soft tissues [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the bony attachment of the BM corresponds to the mucogingival junction [ 5 ]. According to textbook descriptions [ 6 ] and anatomical studies of the ILI [ 2 , 3 , 5 ], the ILI origins at the same level as the mucogingival junction of the mandible pass from the alveolar border of the mandible between the central incisor medially and canine laterally and toward the angle of the mouth or inferior part of the orbicularis oris muscle obliquely. These two muscles, the BM and ILI, thus form the entrance into the bucco-mandibular space.…”
Section: Discussionmentioning
confidence: 99%